Neottiella ricciae (Pyronemataceae, Ascomycota): a hepaticolous fungus in South America - Suarez, Guillermo Martin (2025)
Neottiella ricciae is characterized by asci containing eight smooth, ellipsoid to ovoid ascospores, typically with one rounded side and the other somewhat fusiform. This species is reported for the first time in SouthAmerica, where it was found colonizing a new host, Riccia cavernosa. The present work provides a detailed description of this fungus with photographs of its macroscopic and microscopic features.